THE EXISTENCE OF THE TRADITION OF THE PROHIBITION OF NGIDUL-NGETAN MARRIAGE: AN ANALYSIS OF LIVING LAW AND ʿURF IN ISLAMIC LAW - Pebry Rahmawati; Abdul Fattaah (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the acceptance, response, and practice of the Ngidul Ngetan marriage prohibition in Bangunrejo Village and examine its position from the perspectives of Eugen Ehrlich's Living Law theory and the Islamic legal concept of ʿUrf. The Ngidul Ngetan tradition prohibits marriage between residents of Bangunrejo and Sekaralas villages based on the belief that the south-east directional alignment resembles a sickle shape, symbolizing misfortune. This research employs a qualitative approach with a juridical-empirical design. Data were collected through in-depth interviews with four categories of informants: customary leaders, religious figures, marriageable-age residents, and couples who violated the tradition. Data were analyzed using descriptive-analytical methods through data reduction, categorization, theoretical interpretation, and source triangulation. The findings reveal that the normative strength of the Ngidul Ngetan tradition has significantly weakened, shifting from a sacred norm to a symbolic social norm maintained through respect for ancestors and social harmony rather than fear of supernatural consequences. From the Living Law perspective, this tradition represents living law as it operates without formal enforcement and adapts dynamically. From the ʿUrf perspective, this tradition is categorized as ʿurf ṣaḥīḥ (valid custom) as it does not contradict Islamic principles and promotes social welfare. This research contributes to understanding the harmonious synergy between customary law and Islamic law in shaping legal consciousness in Indonesian society.